Free movement, the welfare state, and the European Union's over‐constitutionalization: Administrating contradictions. (24th March 2017) - Blauberger, Michael; Schmidt, Susanne K.
Abstract : The European Union (EU) has to reconcile free movement rights with national welfare states. Case law of the European Court of Justice (ECJ) has broadened rights to welfare of economically inactive or marginally active EU citizens. Applying the Court's jurisprudence, which is vague and specific at the same time, poses serious challenges for national administrations. Vague criteria for individual assessments have to be translated into mass procedures. And legislative corrections of the case law are often foreclosed given the EU's skewed separation of powers and the over‐constitutionalization of European law, where crucial policy choices are taken by the Court's Treaty interpretation. We compare the British and the German approaches and show that ECJ case law impacts through different channels, but triggers similar challenges for national administrations.